Speech Acts in the Podcast Pasca Laga Bersama Thom Haye & Debutan Pelupessy - Fahrunnisa Haerani; Titi Dewi Rohati; Erniyanti Nur Fatahhela Dewi (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
Speech acts are important in communication as it not only conveys information, but also perform actions and influences hearer. In spontaneous media like podcast, the natural use of language is appropriate for analyzing how intent is conveyed through utterances. The aim of this research is to determine the types of illocutionary acts utterances by Neal, to determine the types of perlocutionary acts utterances by Thom and Joey, and analyze perlocutionary effects successful, or unsuccessful after the speech acts are uttered. This research uses theory of Searle (1979) for categorizing illocutionary acts, Searle (1969) for categorizing perlocutionary acts, and Austin (1962) for identifying the effect of perlocutionary acts. This research uses descriptive qualitative method to find the result. The results show that Neal uses 5 types of illocutionary acts which are representative, directive, expressive, commissive, and declaration. Meanwhile, Thom and Joey us 3 types of perlocutionary acts including verbal perlocutionary, non-verbal perlocutionary, and verbal-nonverbal perlocutionary. Moreover, the perlocutionary effect is said to be successful in line with the speaker’s intention, since out of the 10 data analyzed, there are 8 successful mostly accomplish the expected communicative purpose.